Complete genome sequence of Corynebacterium pseudotuberculosis biovar ovis strain P54B96 isolated from antelope in South Africa obtained by rapid next generation sequencing technology. Issue 2 (September 2012) - Shah Hassan, Syed; Guimarães, Luis; Pádua Pereira, Ulisses; Islam, Arshad; Ali, Amjad; Bakhtiar, Syeda; Ribeiro, Dayana; Rodrigues dos Santos, Anderson; Castro Soares, Siomar; Dorella, Fernanda; Pinto, Anne; Cruz Schneider, Maria; et al.
Abstract TheActinobacteria, Corynebacterium pseudotuberculosis strain P54B96, a nonmotile, non-sporulating and a mesophile bacterium, was isolated from liver, lung and mediastinal lymph node lesions in an antelope from South Africa. This strain is interesting in the sense that it has been found together with non-tuberculous mycobacteria (NTMs) which could nevertheless play a role in the lesion formation. In this work, we describe a set of features ofC. pseudotuberculosis P54B96, together with the details of the complete genome sequence and annotation. The genome comprises of 2.34 Mbp long, single circular genome with 2, 084 protein-coding genes, 12 rRNA, 49 tRNA and 62 pseudogenes and a G+C content of 52.19%. The analysis of the genome sequence provides means to better understanding the molecular and genetic basis of virulence of this bacterium, enabling a detailed investigation of its pathogenesis.